P236 Baricitinib provides better pain relief across all disease activity levels compared with placebo and adalimumab in RA. (20th April 2020) - Taylor (Presenter), Peter C; Pope, Janet; Ikeda, Kei; Zhang, Xiang; Jia, Bochao; Zhang, Hong; Quebe, Amanda; Chen, Yun-Fei; Kannowski, Carol L; Holzkaemper, Thorsten; Cardoso, Anabela; Sebba, Anthony
Abstract: Background: In this post hoc analysis, we assessed relationship between pain improvement and disease activity and evaluated whether baricitinib (BARI) provided additional pain improvement vs. PBO and adalimumab (ADA) across levels of disease activity. Methods: 1, 305 patients on stable background MTX were randomized 3:2:3 (PBO:40-mg subcutaneous ADA every other week:daily, oral 4-mg BARI). Pain was assessed with 0-100-mm VAS; pain improvement (baseline to Week 12) was grouped by ≤ 30%, >30% to ≤ 50%, >50% to ≤ 70%, >70%. Disease activity was measured with CDAI, SDAI, DAS28 with CRP, and DAS28 with ESR. To evaluate change in pain with disease activity, regression was used with continuous change in pain VAS score from baseline to Week 12 as outcome and continuous CDAI/SDAI/DAS28-CRP/DAS28-ESR values, treatment, and interaction term between treatment and disease activity as explanatory variables. Last observation carried forward was used to impute missing values. Pain VAS change (Week 12) was estimated if patients achieved remission (REM)/low disease activity (LDA)/moderate disease activity (MDA) as defined by the corresponding clinical measure. Analyses were not adjusted for multiplicity. Data visualization (percentage of pain VAS improvement vs. disease activity) was created to examine pain improvement with treatment over time. Results: With CDAI, 91%/9% of patients had high disease activity/MDA across all treatments (baseline). Percentage of patients achieving REM with PBO, ADA, and BARI were 2%, 7%, 8%; for LDA: 15%, 27%, 33%; for MDA: 33%, 40%, 38%. At all CDAI values, estimated change in pain VAS for BARI was greater vs. PBO and ADA (Week 12). Similar trends were observed with other measures (Table). BARI demonstrated greater pain improvement vs. ADA and PBO in percentage of patients with ≤30%, >30% to ≤ 50%, >50% to ≤ 70%, and >70% pain improvement from baseline at Week 12. . With CDAI/SDAI, greater differentiation between BARI and ADA was observed as CDAI/SDAI values increased. Conclusion: BARI provided additional pain improvement vs. PBO and ADA when disease activity was controlled, across all levels of disease activity, measured by CDAI, SDAI, DAS28-CRP, or DAS28-ESR (Week 12). Disclosures: P.C. Taylor (Presenter): Consultancies; PCT has been a consultant and/or received research support from: AbbVie, Eli Lilly and Company, Galapagos, and Pfizer. J. Pope: Consultancies; JP has been a consultant and/or has received grant/research support from: AbbVie, Amgen, Bayer, BMS, Eli Lilly and Company, Merck, Novartis, Pfizer, Roche, Sanofi, Sandoz, and UCB. K. Ikeda: Consultancies; KI has been a consultant and/or received research support and/or honoraria from: AbbVie, Astellas Pharma, Bristol-Myers K.K., Chugai Pharmaceutical, Eisai, Eli Lilly and Company, Kyowa Hakko Kir. X. Zhang: Corporate appointments; XZ is an employee of Eli Lilly and Company. Shareholder/stock ownership; XZ is a shareholder of Eli Lilly and Company. B. Jia: Corporate appointments; BJ is an employee of Eli Lilly and Company. Shareholder/stock ownership; BJ is a shareholder of Eli Lilly and Company. H. Zhang: None. A. Quebe: Corporate appointments; AQ is an employee of Eli Lilly and Company. Shareholder/stock ownership; AQ is a shareholder of Eli Lilly and Company. Y. Chen: Corporate appointments; Y-FC is an employee of Eli Lilly and Company. Shareholder/stock ownership; Y-FC is a shareholder of Eli Lilly and Company. C.L. Kannowski: Corporate appointments; CLK is an employee of Eli Lilly and Company. Shareholder/stock ownership; CLK is a shareholder of Eli Lilly and Company. T. Holzkaemper: Corporate appointments; TH is an employee of Eli Lilly and Company. Shareholder/stock ownership; TH is a shareholder of Eli Lilly and Company. A. Cardoso: Corporate appointments; AC is an employee of Eli Lilly and Company. Shareholder/stock ownership; AC is a shareholder of Eli Lilly and Company. A. Sebba: Consultancies; AS has been a consultant and/or speaker for: Eli Lilly and Company, Genentech, and Novartis.